2019
DOI: 10.1111/jce.13829
|View full text |Cite
|
Sign up to set email alerts
|

Ambient fine particulate matter (PM2.5) exposure is associated with idiopathic ventricular premature complexes burden: A cohort study with consecutive Holter recordings

Abstract: Background Epidemiological evidence has shown an association between ambient fine particulate matter (PM2.5) exposure and cardiovascular mortality. Increased ventricular premature complex (VPC) burden can cause left ventricular dilatation and dysfunction. We aimed to investigate the relationship between acute PM2.5 exposure and VPC burden in patients without structural heart disease. Methods We reviewed 26 820 patients who underwent 24‐hour Holter electrocardiogram (ECG) recordings between 1 Jan 2013 and 1 Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In previous studies, we demonstrated that acute PM2.5 exposure is associated with sympathetic activation in a diurnal pattern and that PM2.5 exposure is associated with increased arrhythmia burden. [31,32] These ndings are consistent with many other human observations. [33,34] In the current study, we found similar ndings in rats after acute exposure to PM2.5.…”
Section: Pm25 Exposure and Autonomic Modulationsupporting
confidence: 92%
“…In previous studies, we demonstrated that acute PM2.5 exposure is associated with sympathetic activation in a diurnal pattern and that PM2.5 exposure is associated with increased arrhythmia burden. [31,32] These ndings are consistent with many other human observations. [33,34] In the current study, we found similar ndings in rats after acute exposure to PM2.5.…”
Section: Pm25 Exposure and Autonomic Modulationsupporting
confidence: 92%
“…In previous studies, we demonstrated that acute PM2.5 exposure is associated with sympathetic activation in a diurnal pattern and that PM2.5 exposure is associated with increased arrhythmia burden 14 , 15 . These findings are consistent with many other human observations 34 , 35 .…”
Section: Discussionmentioning
confidence: 84%
“…The alteration of autonomic function after PM2.5 exposures are demonstrated in studies of heart rate variability (HRV) and blood pressure in humans 13 . Our group has previously demonstrated the diurnal change of autonomic modulation after acute PM2.5 exposure as well as its impact on arrhythmia burden 14 , 15 . However, the observed changes in the cardiovascular system are the result of the complex interaction between PM2.5 and many other associated factors.…”
Section: Introductionmentioning
confidence: 97%
“…The study also showed that patients who had previous myocardial infarction were more prone to PMinduced ventricular arrhythmias (32). Tsai et al reported that PM 2.5 exposure was associated with high ventricular premature complex (VPC) burden in patients without structural heart disease (33). The VPC burden is one of the clinical indicators of decreased cardiac function in continuous ECG monitoring (34,35).…”
Section: Epidemiological and Clinical Reportsmentioning
confidence: 98%